The child's interests and the case for the permissibility of male infant circumcision. Issue 7 (22nd May 2013) - Mazor, Joseph
Abstract : Circumcision of a male child was recently ruled illegal by a court in Germany on the grounds that it violates the child's rights to bodily integrity and self-determination. This paper begins by challenging the applicability of these rights to the circumcision debate. It argues that, rather than a sweeping appeal to rights, a moral analysis of the practice of circumcision will require a careful examination of the interests of the child. I consider three of these interests in some detail. The first is the interest in avoiding a moderate decrease in expected future sexual pleasure. I argue that even if such a decrease were to occur, it is not wholly unreasonable to think that this might actually be a good thing for the child. Second, I consider the interest in self-determination. I argue that this interest is not as strong as it might appear because the adult's circumcision decision is subject to a variety of biases and a significant lack of information. Finally, I consider the child's interest in avoiding the future costs of adult circumcision. I argue that this interest becomes much stronger in the religious case because the child is quite likely to choose to become circumcised as an adult. The likelihood of the child choosing circumcision in the religious case also reduces the extent to which infant circumcision violates his interest in self-determination. I conclude that male infant circumcision falls within the prerogative of parental decision-making in the secular case and even more clearly so in the religious case. Finally, I distinguish male circumcision from female genital cutting in several important respects and argue that we can coherently hold that male circumcision is permissible without also endorsing all forms of female genital cutting.